DEVELOPING MONOPOLY GAME TO TEACH SPEAKING SKILL FOR JUNIOR HIGH SCHOOL STUDENTS - Wenny Diah Prameswari; Tyas Alhim Mubarok; Ahmad Saifudin (IKIP Siliwangi, 2024)
The purpose of this research is to develop media that can help English teachers teach speaking in English lessons. Research and development (R&D) is the methodology used in this study. The ADDIE development model was applied in this study. There were qualitative and quantitative data in this research. The qualitative data were obtained from the unstructured interview conducted with the English teacher. The quantitative data were obtained from questionnaires given to instrument expert, media expert, lesson expert and students. Field notes and questionnaires were the research instruments used in this study. The result of instrument validation was 83.33%. The result of media validation was 85%. The result of the learning validation was 95%. It means that the media is categorized as a “very valid” product. The result of the students' responses was 86.96%. It means that the students are categorized as